Yesus Kristus: Satu Pribadi dalam Dua Kodrat - Paulus Edi Nugroho (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2022)
Jesus is a unique person since He has two natures in Himself, namely as God and man. The faith in the two natures of Jesus has been existed since the time of the apostles as could be found in the Scriptures of the New Testament. However, there were other Christological teachings that developed in the early Church. These teachings opposed one nature while emphasized another. As the result, the Church regarded these doctrines as heresies since they contradicted the belief of the apostles.. The concepts of Christology that were classified as heretics include gnosticism, ebionism, and monarchy-modalisticism. As these heresies emerged, the Fathers of the Church appeared to defend the teachings of the Church and maintained the orthodoxy of the faith. Finally, the Church, through the Council of Chalcedon, issued the doctrinal decree enshrined in the Creed, claiming that Jesus is truly both God and man.